The Mining Industry and Corporate Social Responsibility: Evidence from Two Mining Communities in Ghana - Diana Siawor-Robertson; Sefa Awaworyi Churchill (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
There is an ongoing debate on the relevance of corporate social responsibility (CSR) and its ability to provide visible development. In this study, we consider two major mining companies in Ghana, Anglogold Ashanti and Newmont Ghana Gold Limited, and draw on a sample from communities in which these companies operate in order to determine the impact of CSR on various dimensions of community development. We find that, in Ghana, the debate is not about whether CSR is developmental or not but rather what strategies and policies can help increase CSR efficiency. Findings suggest that CSR accounts for several visible infrastructure in mining communities. However, there is a major flaw in empowering community members and improving their livelihoods.
Keywords: 330; Mining; CSR; Ghana